2019
DOI: 10.32604/phyton.2019.06504
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and Biochemical Changes in Agave americana L. Plantlets Induced By Ethyl Methanesulfonate

Abstract: A. americana L. is a crop with very little genetic variability. In order to evaluate the effect of ethyl methanesulfonate (EMS) to induce variability in in vitro plantlets of A. americana, different explants (meristems, leaves and roots) were evaluated for the production of callus. MS medium supplemented with ANA (2.68 μM) and BAP (2.68 μM) was used. Callus obtained from apical meristem were treated with 15 mM EMS for two hours after which shoot formation was induced using 2,4-D (0.11 μM) and BAP (44 μM). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
(27 reference statements)
0
5
0
3
Order By: Relevance
“…Various research works mention that the EMS mutagen increases the activity of the enzyme phenylalanine ammonium lyase (PAL), which is important in wound recovery and as a defence mechanism against infection by pathogens, this finding was corroborated when treating calluses of Agave americana with EMS, the researchers demonstrated that PAL activity increased by 80% [11], results similar to those found by Soleht et al [49], where they observed that the PAL enzyme increased its activity in the rice cultivars Pari Ireng (72%) and Melik (66%) after infection by Xanthomonas oryzae pv. Oryzae.…”
Section: Stress-tolerant and Stress-resistant Plantsmentioning
confidence: 90%
See 4 more Smart Citations
“…Various research works mention that the EMS mutagen increases the activity of the enzyme phenylalanine ammonium lyase (PAL), which is important in wound recovery and as a defence mechanism against infection by pathogens, this finding was corroborated when treating calluses of Agave americana with EMS, the researchers demonstrated that PAL activity increased by 80% [11], results similar to those found by Soleht et al [49], where they observed that the PAL enzyme increased its activity in the rice cultivars Pari Ireng (72%) and Melik (66%) after infection by Xanthomonas oryzae pv. Oryzae.…”
Section: Stress-tolerant and Stress-resistant Plantsmentioning
confidence: 90%
“…Regarding the use of EMS to generate plants resistant to phytopathogens, Sánchez-Martín et al [24] used mutants originated by the action of EMS to identify genes for resistance to various phytopathogens. In addition, Reyes-Zambrano et al [11] evaluated Agave americana L and identified that EMS caused phenotypic modifications in the morphological and morphometric parameters, in addition to an increase in the activity of the enzyme (PAL), which is related to resistance to biotic stress. The use of EMS has been also documented to generate plants resistant to abiotic stress.…”
Section: Main Uses Of Emsmentioning
confidence: 99%
See 3 more Smart Citations